Neuropeptides and G-Protein Coupled Receptors (GPCRs) in the Red Palm Weevil Rhynchophorus ferrugineus Olivier (Coleoptera: Dryophthoridae) - Zhang, He; Bai, Juan; Huang, Shuning; Liu, Huihui; Lin, Jintian; Hou, Youming (Frontiers in Physiology, 2020)
The red palm weevil Rhynchophorus ferrugineus is a devastating, invasive pest that causes serious damages to palm trees, and its invasiveness depends on its strong ability of physiological and behavioral adaptability. Neuropeptides and their receptors regulate physiology and behavior of insects, but these protein partners have not been identified from many insects. Here, we systematically identified neuropeptide precursors and the corresponding receptors in the red palm weevil, and analyzed their tissue expression patterns under control conditions and after pathogen infection. A total of 43 putative neuropeptide precursors were identiﬁed, including an extra myosuppressin peptide was identified with amino acid substitutions at two conserved sites. Forty-four putative neuropeptide receptors belonging to three classes were also identified, in which neuropeptide F receptors and insulin receptors were expanded compared to those in other insects. Based on qRT-PCR analyses, genes coding for several neuropeptide precursors and receptors were highly expressed in tissues other than the nervous system, suggesting that these neuropeptides and receptors play other roles in addition to neuro-reception. Some of the neuropeptides and receptors, like the tachykinin-related peptide and receptor, were significantly induced by pathogen infection, especially sensitive to Bacillus thuringiensis and Metarhizium anisopliae. Systemic identification and initial characterization of neuropeptides and their receptors in the red palm weevil provide a framework for further studies to reveal the functions of these ligand- and receptor-couples in regulating physiology, behavior, and immunity in this important insect pest species.